School as a Source of Difficult Situations - Leśniak, Barbara (INSTED: Interdisciplinary Studies in Education & Society, 2015)
The psychological and pedagogical literature, especially the one that refers to criminogenic behaviours, shows that difficult situations belong to factors, which often have a significant impact on the behaviour that is not compatible with the binding standards. According to J.K. Gierowski (1996, p. 137 and n.) the culprit is a person who, being in a difficult situation, tries to solve their problems arising therefrom in a disadvantagous way both for them and for others, breaching the generally adopted rules of behaviour. Depending on a development stage it is possible to indicate various sources of difficult situations. In the literature the attention is turned to the fact that for adolescents one of the main sources of difficult situations (stress) are the following: school and relations with peers and with parents (see Talik, Szewczyk 2009). The aim of the research presented in this article was to establish types of school situations that are perceived by pupils as difficult and which can generate violent behaviour. The execution of this task has not only cognition dimension, but also the application one.